Factors Affecting the Implementation of Enterprise Systems Within Government Organisations in New Zealand - Vevaina, Paeterasp Darayas (Auckland University of Technology, 2007)
The 1990's saw a rapid growth in the use of Enterprise Systems by organisations to undertake quick and strategic decisions. Significant to the use of Enterprise systems, is their implementation in the organisation. The increased use of paper documents in government organisations and the augmented implementation rate of Electronic Document Management Systems within government organisations in New Zealand, is what triggered this research and subsequently the framing of the research objectives and thereby the research question. This research encompasses the factors which affect the implementation process of an Enterprise Document Management System and thereby render it a success or a failure. The study used an ethnographic approach in order to introduce rigour in the research. The data was collected by conducting eight semi-structured interviews at the client organisation. The interviews were transcribed and later coded using an open - coding methodology. A thematic analysis based schema was developed to later analyse the coded data.The research found that, factors such as change management, behaviour management / emotions, communication, implementation process approach and system functionality had profound effects on the implementation success of the Electronic Document Management System in the research organisation. The thesis has been mostly written in the first person to represent the author's interpretation of the implementation process and its related factors.
Keywords: Ethnography; Interviews; Enterprise Systems; Implementation; Nvivo; Thematic analysis